Glycogen synthase kinase-3β (GSK-3β) inhibitors from soil actinomycetes of Sabah rainforests : screening, purification and identification - Fauze Mahmud (2015)
Glycogen Synthase Kinase-3 (GSK-3) is a multitasking enzyme involved in various processes cell. It is expressed in two isoforms in mammalian cells; GSK-3α and GSK-3β. Dysregulation of GSK-3 is a causal factor of diseases such as cancer and diabetes. In drug discovery, GSK-3β is usually being targeted as its activity is more understood compared with GSK-3α. Small molecule originated from nature is regarded as the best inhibitor for GSK-3β that be used for treatment due to their novel structural features and potent activity. Actinomycetes are recognized as prolific producers of active compounds, including potent GSK-3β inhibitor such as staurosporine and manzamine A. External factors such as nutrient availability and pH may influence the production of secondary metabolites by actinomycetes. GSK-3β inhibitors were previously identified in Streptomyces sp. isolated from primary rainforests of Sabah. Due to unexplored potential of actinomycetes from Sabah rainforests, the possibility of finding more inhibitors from actinomycetes of Sabah is promising. In this study, 640 strains of actinomycetes were isolated from 156 soil sample of different forest types in Sabah. Kruskal-Wallis analysis revealed that a large number of isolated strains from secondary forest in which significantly related to the soil pH. Slightly acidic soils were found to yield more strains compared with alkaline soils. Based on the preliminary screening using a yeast-based assay of 505 strains, 14 positive strains were identified. Three strains (FA013, FH025 and H11809) were chosen to be partitioned using LLE. Of the three, H11809 was chosen to be further fractionated using column chromatography due to consistent and potential inhibitory activity. Fractionation of H11809 chloroform extract yielded two active fractions; F4 and F8, in which F8 showed no toxic activity against yeast. Further analysis of F8 using FTIR revealed that carbonyl ester as the major functional group. It was supported by GCMS in which carbonyl ester is the functional group of major compound; dibutyl phthalates (SI >90 %). Carbonyl group was reported to facilitate the binding of numerous inhibitors with GSK-3β. Minor compound; cyclo-leu-pro (SI >80 %), was also chosen to be further studied due to the presence of carbonyl group as well (carbonyl amide). Identification was supported by spiking using commercially-purchased pure compounds. Both compounds were shown to inhibit the activity of GSK-3β based on a yeast-based and kinase assays. Michaelis-Menten and Lineweaver-Burke plots showed that dibutyl phthalates inhibited GSK-3β with mixed inhibition and cyclo-leu-pro uncompetitive inhibition. IC50 values of dibutyl phthalates indicated active (IC50 =3.1 μM) inhibitory activity against GSK-3β while cyclo-leu-pro exhibited moderate inhibition (IC50 =12.94 μM). In conclusion, GSK-3β inhibitors were successfully identified from actinomycetes strain H11809, and may serve as a good lead to be further developed since non-ATP competitive inhibitors are the main interests in drug discovery.